A common indel polymorphism of the Desmoglein-2 (DSG2) is associated with sudden cardiac death in Chinese populations. (August 2019) - Zou, Yan; Zhang, Qing; Zhang, Jianhua; Chen, Xuekun; Zhou, Wei; Yang, Zhenzhen; Yang, Qi; Yu, Huan; Li, Lijuan; He, Yan; Li, Chengtao; Zhang, Suhua; et al.
Highlights: The rs397729601 polymorphism is significantly associated with SCD susceptibility. Genotypes of rs397729601 are correlated with DSG2 expression in human heart. The rs397729601 could regulate DSG2 expression through via miR-933-3p. The rs397729601 may be used as a potential marker for molecular diagnosis of SCD. Abstract: Sudden cardiac death (SCD) is referred to as sudden and unexpected death caused by cardiovascular diseases, in which a person preexisted heart disease or not. Compelling evidence indicates that SCD etiology have been predominantly affected by host genetic factors. However, how genetic variants play roles in the inherited risk component of SCD are still largely unknown. It has been reported that Desmoglein-2 ( DSG2 ) mutations might be related to sudden death. In the present study, we used a candidate gene approach to investigate the associations between rs397729601 (a 2-base pair indel polymorphism) mapping to the 3′UTR of DSG2 with the risk of SCD. It is shown by logistic regression analysis that the risk of SCD has been significantly increased by the deletion allele of rs397729601 [odds ratio (OR) = 1.51; 95% confidence interval (CI) = 1.12–2.05; P = 0.00559]. Additional genotype-phenotype analysis was performed to evaluate the mRNA level, revealing that human myocardium tissues with the deletion allele showed higher expression of DSG2. Dual luciferase activity analysis was conducted in an in vitro reporter gene system, suggesting that DSG2 expression could be regulated by rs397729601 which interrupted the binding of miR-933-3p with DSG2 . We concluded that rs397729601 may affect the expression of DSG2 through miR-933-3p regulation, contributing to SCD susceptibility. Thus, rs397729601 may be used as a potential marker for molecular diagnosis and genetic counseling of SCD. Our findings need to be validated through replication and further functional studies.